Ab Initio and DFT Study of Chinesin I and Chinesin II - Mammino, Liliana (Current Physical Chemistry, 2015)
Chinesin I and chinesin II are acylphloroglucinols of natural origin differing only by the length of their acyl chains. They exhibit antimicrobial and antiviral activities, including inhibitory effects on the replication of the vesicular stomatitis and herpes simplex viruses. Their structures (different from those of the acylphloroglucinols so far investigated computationally) combine a variety of factors with significant influence on conformational preferences: the presence of a keto O replacing one of the phenol OH ortho to the acyl chain, which removes one of the possibilities for the formation of the intramolecular hydrogen bond between the sp2 O of the acyl chain and an ortho OH, typical of acylphloroglucinols; the presence of a substituted pentagonal ring attached to the phloroglucinol moiety through a methylene bridge; and the presence of a prenyl chain, whose bond can interact with a phenol OH. Methods: The two compounds were studied at the Hartree Fock (HF/6-31G(d,p)) and Density Functional Theory (DFT/B3LYP/6-31+G(d,p)) levels, in vacuo and in three solvents – chloroform, acetonitrile and water. Calculations in solution utilized the Polarizable Continuum Model (PCM). Results: The results show fair correspondence with the patterns identified for acylphloroglucinols and, in particular, for acylphloroglucinols in which the OH at C6 is replaced by a keto O. Conclusion: The close similarities in the conformational preferences and molecular properties of the two compounds confirm scarce influence by the nature of the acyl chain, when it does not contain groups which can interact with the phloroglucinol moiety. They may also be considered responsible for the similarities in the biological activities of the two molecules.
Keywords: Acylphloroglucinols